Effects of Solanum glaucophyllum toxicity on cell proliferation and apoptosis in the small and large intestine of rabbits - Zanuzzi, Carolina Natalia (2012)
Vitamin D regulates mineral homeostases and enterocyte proliferation and differentiation. Hypervitaminosis D generates changes in cell proliferation, differentiation and apoptosis in several organs. We analysed morphometric parameters and proliferative and apoptotic indices in the intestinal epithelium of rabbits with hypervitaminosis D induced by the chronic treatment with the calcinogenic plant Solanum glaucophyllum. Rabbits were treated for 15 or 30 days. A group was treated for 15 days and led to possible recovery for 30 days. Another group was nutritionally restricted for 30 days. Morphological, morphometric, proliferative and apoptotic changes were found in the treated animals. Mild atrophy and reduced proliferation was found in the jejunum and ileum. Apoptosis increased in the crypts of the ileum and in the superficial epithelium and crypts of the rectum. Most of the alterations were partially recovered. The possible involvement in these changes of the hypervitaminosis D-like state induced by S. glaucophyllum is discussed.